ANALISIS RESIKO KECELAKAAN KERJA PADA PROYEK PEMBANGUNAN GEDUNG KULIAH, LABORATORIUM, DAN BENGKEL JURUSAN TEKNIK MESIN, POLITEKNIK NEGERI MALANG DENGAN METODE FAULT TREE ANALYSIS (FTA) - Bagus Firman Mahardika; Samsul Arifin; Paksitya Purnama Putra (Fakultas Teknik, Universitas Wiraraja, 2021)
Occupational safety and health are things that need attention.Zaini Z. Ikhsan, chairman of the Occupational Safety and Health Expert Association, said that every year 96,000 work accident cases occur. Importance awareness of occupational safety and health to provide a sense of security and prevention of workplace accidents can increase work productivity.This study aims to analyze the risk of work accidents in the construction projects of lecture buildings, laboratories, and workshops majoring in Mechanical Engineering, State Polytechnic of Malang. The method used is the Fault Tree Analysis (FTA) method.The results of the study showed that 2 of the 34 risks studied had a significant risk impact, namely workers injured by exposure to iron in the commissioning work and workers falling on the ceiling work. The two risks that have the most significant impact are included in quadrant 1 on the risk map.Risks that go into quadrant 1 means that these risks must be taken seriously and require quick treatment.